Implementation of the Child Protection Law in Cases of Child Violence - Rosemaria Rosemaria (PT. Anagata Sembagi Education, 2024)
The Child Protection Law in Indonesia is a legal foundation to guarantee children's rights from violence, whether physical, psychological, or sexual. However, the high rate of violence against children indicates a gap between legal norms and implementation in the field. This article aims to analyze the implementation of Law Number 35 of 2014 concerning Child Protection, especially in handling cases of violence against children. Using qualitative research methods through case studies and in-depth interviews, it was found that the implementation of this law still faces various obstacles, including weak coordination between institutions, lack of understanding of law enforcement officers regarding the substance of child protection law, and minimal community involvement in monitoring and reporting cases. This article suggests the need to increase the capacity of law enforcement, public awareness campaigns, and strengthen synergy between institutions to make legal protection for children effective. This research provides academic and practical contributions to improving the child protection system in Indonesia.